Building Indonesia's Golden Generation through Financial and Investment Education from an Early Age - Afriani; Fajria; s, ahmad; Rizki amalia; Mardiyah (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2026)
Limited financial literacy among school-age children remains a challenge in developing responsible financial behavior from an early age. Many students still have difficulty distinguishing between needs and wants and understanding the importance of saving. This community service program aimed to improve the financial literacy of students at MI Darul Imam and MTs Darul Imam in Palu City through interactive and participatory learning activities. The program was implemented using lectures, group discussions, storytelling, and educational games adapted to students’ age and level of understanding. The findings showed that the activities improved students’ understanding of basic financial concepts and encouraged them to apply more disciplined financial behavior in daily life. Teachers also gained insight into integrating financial literacy into classroom learning. Overall, the program demonstrated that interactive financial education can effectively foster early financial awareness, strengthen positive saving habits, and support the development of a financially responsible young generation in line with the vision of Indonesia Golden Generation 2045.